A Systematic Review of the Effects of Brain Gymnastics on Cognitive Function and Anxiety in Menopausal Women - Atma Deviliawati; Aris Citra Wisuda; Citra Suraya; Maya Fadlilah; Apriyanti Aini; Zuhana Zuhana; Margareta Haiti; Novita Anggraini (YCAB Publisher, 2026)
Background: Menopause is a natural phase in a woman's life marked by significant hormonal, physical, and psychological changes. These changes often result in symptoms such as cognitive decline, mood disturbances, sleep disorders, and increased anxiety, which can negatively impact overall quality of life. One non-pharmacological approach to mitigate these effects is brain gymnastics, a form of cognitive stimulation exercise aimed at maintaining or improving brain function. Objective: This systematic review aims to evaluate the effects of brain gymnastics on cognitive function and anxiety levels in menopausal women. Methods: This systematic review followed PRISMA guidelines and involved a comprehensive literature search across databases such as PubMed, ProQuest, ScienceDirect, DOAJ, Wiley, and Garuda, using the Publish or Perish tool. Studies published between 2019 and 2024 were included, and inclusion/exclusion criteria were based on the PICOS framework. Relevant articles were screened, and those meeting the criteria underwent full-text review and analysis. Results. Out of 1471 initially identified studies, 9 met the inclusion criteria and were analyzed in this review. The findings indicate that brain gymnastics interventions have a positive impact on improving cognitive performance and reducing anxiety symptoms in menopausal women. Regular participation in these exercises contributes to enhanced memory, attention, mood regulation, and overall mental well-being. Conclusion: rain gymnastics is a beneficial non-pharmacological intervention for cognitive decline and anxiety in menopausal women. Its effectiveness is influenced by factors like age and consistent practice. Regular participation may enhance cognitive health and emotional stability during and after menopause.